2022
DOI: 10.3390/plants11141788
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Mosaic Virus Infection of Chrysanthemums in Thailand: Development of Colorimetric Reverse-Transcription Loop-Mediated Isothermal Amplification (RT–LAMP) Technique for Sensitive and Rapid Detection

Abstract: We detected tobacco mosaic virus (TMV), a member of the genus Tobamovirus and one of the most significant plant-infecting viruses, for the first time in a chrysanthemum in Thailand using reverse-transcription polymerase chain reaction (RT–PCR). The TMV-infected chrysanthemum leaves exhibited mosaic symptoms. We conducted a sequence analysis of the coat protein (CP) gene and found that the TMV detected in the chrysanthemum had 98% identity with other TMV isolates in GenBank. We carried out bioassays and showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The final results showed that ‘Jianyunxiang’, ‘Quanxiang Wansheng’ and ‘Quanxiang Chongtian’ were only infected with CVB, and ‘Chixian Jingou’ was only infected with TAV and CVB [ 85 ]. Supakitthanakorn et al ground the chrysanthemum leaf that tested positive for TMV with 0.1 M phosphate buffer and used it to mechanically inoculate carborundum-dusted chrysanthemum leaves, confirming the pathogenicity of TMV in chrysanthemums [ 86 ].…”
Section: Research Progress In Chrysanthemum Virus Detection Technologymentioning
confidence: 99%
“…The final results showed that ‘Jianyunxiang’, ‘Quanxiang Wansheng’ and ‘Quanxiang Chongtian’ were only infected with CVB, and ‘Chixian Jingou’ was only infected with TAV and CVB [ 85 ]. Supakitthanakorn et al ground the chrysanthemum leaf that tested positive for TMV with 0.1 M phosphate buffer and used it to mechanically inoculate carborundum-dusted chrysanthemum leaves, confirming the pathogenicity of TMV in chrysanthemums [ 86 ].…”
Section: Research Progress In Chrysanthemum Virus Detection Technologymentioning
confidence: 99%
“…To determine possible cross reactivity to other viruses and viroids, the positive cDNA of other viruses and viroids including cucumber mosaic virus (CMV), chrysanthemum virus B (CVB), tobacco mosaic virus (TMV), turnip mosaic virus (TuMV) and chrysanthemum chlorotic mottle viroid (CChMVd) were examined. CMV was isolated from tobacco while CVB, TMV, TuMV and CChMVd were isolated from chrysanthemum (Supakitthanakorn et al 2022a;Supakitthanakorn et al 2022b). Total RNA of all viruses and CChMVd were isolated from infected leaves by using TRIzol ® Reagent (Invitrogen, Waltham, USA) according to the manufacturer's instructions and then used as templates for cDNA synthesis by using ReverTra Ace TM qPCR Master Mix with gDNA Remover (Toyobo, Osaka, Japan) according to the manufacturer's instructions.…”
Section: Specificity Assaymentioning
confidence: 99%
“…Moreover, to reduce the risk of contamination and enhance the rapidness, one step RT-LAMP was developed to detect pepino mosaic virus (PepMV) from tomato (Hasiów-Jaroszewska and Borodynko 2013). Recently, LAMP has been widely used to detect plant pathogens, especially viruses and viroids (Panno et al 2020), such as, tobacco mosaic virus (TMV) (Supakitthanakorn et al 2022b), maize chlorotic mottle virus (MCMV) (Liu et al 2016), mirafiori lettuce big vein virus (MiLBVV) (Almasi 2017), columnea latent viroid (CLVd) (Bhuvitarkorn et al 2019) and plum viroid I (PVdI) (Bester and Maree 2022). To avoid post-amplification contamination, the colorimetric LAMP has been applied to detect viruses and viroids (Bhuvitarkorn et al 2019;Supakitthanakorn et al 2022b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation

Journal of Plant Protection Research

Supakitthanakorn,
Vichittragoontavorn,
Kunasakdakul
et al. 2022
“…TMV is the first discovered virus that infects more than 150 different species 6 . TMV is transmitted by mechanical inoculation, grafting, and by many species of aphids in a no persistent manner 7 , and induces mosaic-like mottling and discoloration on the leaves 8 .…”
Section: Introductionmentioning
confidence: 99%